2007
DOI: 10.1016/j.micinf.2006.10.015
|View full text |Cite
|
Sign up to set email alerts
|

Lipid rafts play an important role in the early stage of severe acute respiratory syndrome-coronavirus life cycle

Abstract: Lipid rafts are involved in the life cycle of many viruses. In this study, we showed that lipid rafts also play an important role in the life cycle of severe acute respiratory syndrome (SARS)-coronavirus (CoV). Cholesterol depletion by pretreatment of Vero E6 cells with methyl-beta-cyclodextrin (MbetaCD) inhibited the production of SARS-CoV particles released from the infected cells. This inhibition was prevented by addition of cholesterol to the culture medium, indicating that the reduction of virus particle … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
191
5
3

Year Published

2009
2009
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 162 publications
(210 citation statements)
references
References 30 publications
(37 reference statements)
11
191
5
3
Order By: Relevance
“…3A). This finding is compatible with reports that lipid rafts are required for virus entry but not for virus release in MHV (48) and SARS-CoV (49). Although the presence of RNA is necessary for efficient N-N interaction, we found that M-M or M-N interaction does not require RNA (Fig.…”
Section: Discussionsupporting
confidence: 93%
“…3A). This finding is compatible with reports that lipid rafts are required for virus entry but not for virus release in MHV (48) and SARS-CoV (49). Although the presence of RNA is necessary for efficient N-N interaction, we found that M-M or M-N interaction does not require RNA (Fig.…”
Section: Discussionsupporting
confidence: 93%
“…Moreover, upon M␤CD treatment, membrane cholesterol levels remain low for 9 to 12 h (25,43). Cells were treated with M␤CD (10 mM) for 1 h either 1 h prior to or 1 h after infection with BDV (MOI, 0.1), and at 48 h p.i., we examined the number of BDV-infected cells based on expression of BDV N as determined by IFA (Fig.…”
Section: Effect Of M␤cd On Bdv Infectionmentioning
confidence: 99%
“…Human immunodeficiency virus type-1 infection requires cholesterol, both in the target cell membrane and the viral envelope (Guyader et al, 2002;Liao et al, 2001Liao et al, , 2003. Many viruses require cholesterol in the target cell membrane, such as Semliki Forest virus (Phalen and Kielian, 1991;Ahn et al, 2002), severe acute respiratory syndrome-coronavirus (Li et al, 2007) and SV40 virus (Anderson et al, 1996). For influenza virus and duck hepatitis B virus, the presence of cholesterol in its viral envelope is critical, but it is not essential in the target cell (Sun and Whittaker, 2003;Funk et al, 2008).…”
Section: Introductionmentioning
confidence: 99%